The Effects of Some Different Cultural Techniques on the Transmission and Infectious Development of Pepper Yellow Leaf Curl Indonesia Virus on Red Chili - Suparman, Suparman; Arsi, Arsi; Pujiastuti, Yulia; Pratama, Rahmat (AGRIVITA Journal of Agricultural Science, 2024)
An experiment is conducted to investigate the effects of cultural techniques on pepper yellow leaf curl disease caused by Pepper yellow leaf curl Indonesia virus (PepYLCIV). The investigation is conducted in the area where the disease has been endemic and Bemisia tabaci is abundant. Four cultural techniques are applied in separate lands and cannot interfere with each other. The methods applied are seed treatment, intercropping, trap cropping, and physical barrier. Seeds harvested from infected plants are used for seed treatment experiments, and local farmers use commercial sources for other experiments. The results confirmed that PepYLCIV was a seed-borne virus affected by hot water treatment at 65oC for 30 minutes. Turmeric crude extract could reduce the incidence and severity of the disease. The tomato is a better intercrop than eggplant, mung bean, and soybean in reducing disease incidence, but their effects on disease severity and yield reduction were not significantly different. Basil and marigolds were better barrier crops compared to cosmos and zinnia. A 125 cm high physical barrier using 50 mesh cheesecloth could reduce the disease incidence, but not the lower ones. Under different cultural techniques, PepYLCIV causes a 40.00–52.32% chili yield reduction.